The Effectiveness of Meloxicam Adjuvant Therapy to Improve Cognitive Function of Schizophrenic Patients - Islamy, Nabila Nur Bilqis; Nugroho, I Gusti Bagus Indro; Herdaetha, Adriesti (Universitas Airlangga, 2023)
Highlights:1. Schizophrenic patients have cognitive dysfunction.2. Meloxicam, as an adjuvant therapy, can improve cognitive function in schizophrenic patients. AbstractIntroduction: Schizophrenia is a chronic psychotic disorder triggered by genetic and environmental factors such as an inflammatory response. The inflammatory response in schizophrenic patients increases with cognitive decline. Meloxicam is a non-steroidal anti-inflammatory drug (NSAID) group with Cyclo-oxygenase (COX-2) inhibitory activity and can suppress the production of inflammatory cytokines. This study aimed to determine the efficacy of Meloxicam as an adjuvant therapy to improve cognitive function in schizophrenic patients.Methods: This was a quasi-experimental study using a single-blind, pretest–post-test design. The sample size in this study was 34 subjects who had met the inclusion and exclusion criteria. All samples were divided into two groups, namely the treatment group, with as many as 17 subjects receiving additional therapy with Meloxicam 15 mg/day for 4 weeks, and the control group, with 17 subjects. The score of the Schizophrenia Cognition Rating Scale (ScoRS) was assessed before and after therapy. Data analysis used SPSS 25.0. In both groups, the SCoRS score was different.Results: In the treatment group, there was a decrease in the SCoRS score that was greater than in the control group. There was a statistically significant difference with p = 0.002 in decreasing SCoRS scores.Conclusion: In the treatment group, there was a decrease in the SCoRS score that was greater than in the control group. There was a statistically significant difference with p = 0.002 in decreasing SCoRS scores.